PENERAPAN SANKSI TERHADAP PENYIMPANGAN PENYIDIK POLRI DALAM MENANGANI PERKARA - Dani Durahman (Universitas Batanghari Jambi, 2016)
The functionsand tasks ofthe national policeset upby article13of law No.2of 2002onthe police forcethat iskeeping thesecurityand orderof society,enforce the law,and provide protection,shelter, and serviceto the community.Froma series of tasksthat isone of the tasksthe policeenforce the law,police andlaw enforcement agenciesasauthorizedin the processof investigationthatiscentralor